Etika Sosial-Ekonomi Islam dan Ketahanan Psikologis: Menjelajahi Hubungan Antara Iman, Kesejahteraan, dan Kesehatan Masyarakat - Fidya Pramesti; Muhammad Furqan (CV SCRIPTA INTELEKTUAL MANDIRI, 2025)
This study explores the interconnection between Islamic socioeconomic ethics and psychological resilience, emphasizing the integration of faith-based values in promoting community mental health. Grounded in qualitative inquiry, the research examines how principles such as justice (adl), equity, and social responsibility embedded in Islamic economic practices particularly zakat, infak, and waqf contribute to psychological stability and collective well-being. Empirical data from national reports indicate that effective zakat distribution enhances financial security, reduces anxiety, and reinforces trust within communities. Furthermore, the spiritual dimension, encompassing gratitude (shukr), patience (sabr), and reliance upon God (tawakkul), serves as a psychological buffer against economic distress. The integration of these spiritual and ethical elements fosters adaptive coping, social solidarity, and a renewed sense of meaning among individuals facing socioeconomic challenges. The study concludes that merging Islamic ethical economics with spirituality provides a holistic model for sustainable mental health promotion. Such an integrative framework aligns moral responsibility, economic justice, and psychological resilience, offering significant implications for public policy and community-based interventions in Muslim-majority societies.